Hubungan antara Lingkungan Keluarga dan Prestasi Pendidikan Islam pada Siswa di Sekolah Menengah - Siti Mariatul Kiftiah (PT Barkah Ilmi Fiddunya, 2024)
The family environment is the primary and initial setting for introducing knowledge to children, especially religious knowledge. This study aims to determine how the family environment can influence children's Islamic religious education. The research uses a literature review method. Islamic religious education is a crucial aspect of children's spiritual and moral development, where the role of the family is essential in this process. By reviewing various literatures and previous studies, this article identifies how parental upbringing, their involvement in religious practices, and the values applied at home affect children's religious education. The study finds that families actively engaged in religious activities, providing good role models, and creating a conducive environment for religious learning can enhance children’s understanding and practice of Islamic teachings. Conversely, a lack of family support or conflicts in religious values can hinder the development of children's religious education. These findings highlight that the family environment plays a crucial role in shaping children's religious education and emphasize the need for greater efforts to support the family's role in Islamic religious education